The Scientific Literacy Test Instrument on Particle Dynamics for High School Students - Mustika Wati; Saiyidah Mahtari; Anis Muthi'ah; Dewi Dewantara; Suharno (Asian Journal of Assessment in Teaching and Learning, 2023)
The measurement of scientific literacy is very focused, this is shown by the urgency of preparing scientific literacy test instruments. This research develops a proper scientific literacy test instrument on particle dynamics material. This research is a development research adapted from the Borg and Gall model. The test subjects of this study were 202 students. Design validation, instrument validity, instrument reliability, instrument difficulty level and instrument differentiability are data analysis techniques. The product produced is a material science literacy test instrument for particle dynamics totaling 10 questions in the form of reasoned multiple choice questions. The results showed that (1) the questions were in the valid category, (2) had reliability with very good criteria of 0.83 (3) the difficulty level of the questions obtained 1 item in the difficult category and 11 questions with moderate criteria, (4) the results of the discriminating power of the questions show that there are 2 questions with sufficient discriminating power so that the items can still be used and there are 2 items with bias so that 2 items are discarded. It can be concluded that the developed scientific literacy test instrument can be used to measure students’ scientific literacy competence.